Clinical and Molecular Findings in Mendelian Susceptibility to Mycobacterial Diseases: Experience From India - Taur, Prasad D.; Gowri, Vijaya; Pandrowala, Ambreen Abdulwahab; Iyengar, Vaishnavi V.; Chougule, Akshaya; Golwala, Zainab; Chandak, Shraddha; Agarwal, Reepa; Keni, Purva; Dighe, Neha; Bodhanwala, Minnie; Prabhu, Shakuntala; et al. (Frontiers in Immunology, 2021)
Mendelian Susceptibility to Mycobacterial diseases (MSMD) are a group of innate immune defects with more than 21 genes and 36 clinical phenotypes identified. Defects in the IL-12/23-IFN-γ axis leads to an increased susceptibility to intracellular pathogens like mycobacteria including attenuated Mycobacterium bovis-Bacillus Calmette-Guérin (BCG) vaccine strains and non-tuberculous environmental mycobacteria (NTM), Salmonella, fungi, parasites like Leishmania and some viruses, in otherwise healthy individuals. Mutation in the IL-12Rβ1 gene is the commonest genetic defect identified. This retrospective study reports the clinical, immunological and molecular characteristics of a cohort of 60 MSMD patients from 11 centres across India. Microbiological confirmation of mycobacterial infection by PCR in addition to histopathologic and microbiologic findings of acid-fast bacilli (AFB) was followed by immunologic workup including lymphocyte subset analysis, nitroblue tetrazolium (NBT) test, immunoglobulin levels, and flow-cytometric evaluation of the IL-12/23 pathway and genetic analyses. Disseminated BCG-osis was the commonest presenting manifestation (75%) with a median age of presentation of seven months due to the practice of BCG vaccination at birth. This was followed by infection with Salmonella and non-typhi Salmonella (12%), Cytomegalovirus (CMV) (10%), Candida (7%), NTM (5%), and Histoplasma (2%). More than half of the patients were infected by more than one organism. This study is the largest cohort of MSMD patients reported from India to our knowledge and highlights the importance of having a high index of suspicion in patients presenting with adverse effects to BCG vaccination and investigating the IL12-23 pathway in all patients with a clinical suspicion of MSMD irrespective of age.